Домінування андрогенів і синдром полікістозних яєчників у жінок репродуктивного віку - Семенюк, Л. М.; Яроцький, М. Є. (Clinical Endocrinology and Endocrine Surgery, 2013)
Clinical manifestations of polycystic ovary syndrome (PCOS), approaches to its diagnosis and treatment are revealed. It is shown that a comprehensive diagnosis of PCOS and differentiated approaches to correcting androgen dominance in this pathology allow quite successfully to treat patients with menstrual irregularities and restore reproductive function.